(3QSGdI aj Yde GdMSGHs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdMSGH aj GddZI GdYO haj GdGUWdGM Cgd GdMSGH YHGQI Yf bGfhf JYQa HgG CYOGO eLghdI GYde Cf GdMSGH GHJOGA djS dgG GfJgGA hCf dg eQGJH ef CUhd haQhY CeG GdCUhd s
(3BNQgG (B:s
(3aGdMce cPdc aj LejY eG PcQfG ef GdCMhGd GdCQHYI ZGjI eG aj GdHGH Cf JCNP dcd hGMO eGFI aj GdeBJ hHcd hGMO CdaG aj GdCdha heG PcQg GdeUa aj cjajI GdYed Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\257s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs